PERANCANGAN DAN IMPLEMENTASI SISTEM KATALOG BUKU SECARA ONLINE PADA PERPUSTAKAAN DAERAH PROVINSI LAMPUNG - Neni Purwati (IIB Darmajaya, 2011)
Based on directly observation in Central Library Lampung Province, it seen that the service for visitor particularly in departement of book circulation, book processing and procurement, and book maintenance are still done manually. Futhermore, it probably causing some problems, for instance, when visitor need some information, library staff can make mistake and the service is not fast. The alternative solution to solve this problem is the utilization of information technology in particular implementing database that base on computer to fullfill user or visitor need. By using server side program on Microsoft Windows System Operation, web base interface, sorting method, and search engine are hoped able to reduce the mistake and make user or visitor able to search the information about the book easly. Keyword : Search Engine, Katalog Buku, Online